Membership Questionnaire Summary. - Bower, James B.; Dunn, Clarence L.; Fritzemeyer, Joe R. (The Accounting Review, 1967)
Abstract The Committee on Long Range Planning and the Executive Committee have substantial data not previously available to assist in fulfilling their responsibility to the membership. Special thanks are extended to the hundreds of members who assisted by sending in a completed questionnaire.